Impact of Exercise on Lower Activity Levels in Children with Acute Lymphoblastic Leukemia: A Randomized Controlled Trial from Turkey - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
This randomized, controlled experimental study was carried out to determine the effects of an exercise program on both physical parameters and the quality of life of children with acute lymphoblastic leukemia (ALL). A total of 41 children with ALL (20 trial and 21 control cases) at two university hospitals were accepted into the study. Due to the demise of one of the children in the trial group, the study was completed with 19 trial and 21 control patients, a total of 40 children and their parents. Regular and systematic exercise regimens implemented by children with ALL have resulted in improved testing results, enhanced physical performance, and better laboratory results compared with a control group and to children's scores before the initiation of such a program.
Keywords: children with ALL; exercise tolerance; muscle strength; quality of life; QUALITY-OF-LIFE; CANCER; INTERVENTION; THERAPY; PEDSQL(TM)-4.0; PERFORMANCE